Hypovitaminosis D Is Not A Risk Factor for Stress Fracture or Reaction in NCAA Division I Track And Field. Issue 7 (29th July 2019) - Lindsay, Adam; Jalali, Omid; Korber, Shane; Romano, Russ; Kang, Hyunwoo Paco; Tibone, James E.; Weber, Alexander E.; Gamradt, Seth C.
Objectives: Most research on the role of vitamin D on skeletal health has been dedicated to the elderly for fracture prevention. However, there is a paucity of research examining the role of vitamin D in elite track and field athletes. The objective of this study was to evaluate the prevalence of stress reactions and fractures in NCAA Division I track and field athletes, and to determine the relationship between fractures and serum vitamin D levels. Methods: After IRB approval, we evaluated data for men's and women's outdoor track and field teams from 2015-2018 at a large NCAA Division I athletics program. Vitamin D levels were drawn during pre-season annual physicals. The cutoff for hypovitaminosis D was set at 40 nmol/L. Demographic and athletic tenure data were recorded and analyzed, and competitive events were grouped into one of four categories: 1) running events, 2) jumping events, 3) throwing events, and 4) multiple event types. Student T tests, chi-squared tests, and multivariate logistic regression were performed. Results: Of the 148 athletes analyzed, greater than 50% had hypovitaminois D (Figure 1). There were 29 (19.6%) athletes sustained a stress fracture or stress reaction. There was no difference in mean vitamin D levels in the injured group vs the non-injured group (43.55 ± 11.97 vs. 39.61 ± 12.32, respectively; p=0.122). Additionally, multivariate logistic regression failed to demonstrate an association between stress fracture or reaction incidence and vitamin D status, age, BMI, or event type (p>0.05 for all). Conclusion: These data suggest that NCAA Division I track and field athletes suffer a high rate of stress fractures and reactions, though those with hypovitaminosis D are not at increased risk of these injuries. This is the first study to demonstrate this in a heterogeneous population of elite athletes. Future studies investigating other modifiable risk factors for fracture in this population are warranted to prevent the health and athletic consequences of these fractures.